Josef Frank - Falsterbovillorna - Bergquist, Mikael 1961-; Michélsen, Olof 1962- (Arkitektur förlag, 2017)
Between 1924 and 1936, the Austrian-born architect and designer who became a Swedish citizen, designed five summer houses in Falsterbo. The architecture of the Falsterbovillas is an architecture that challenges pervasive notions of beauty and function, modern and traditional at the same time